Socialno doživljanje - Tomc, Gregor (Družboslovne razprave, 2008)
The author defines the world as a totality of physical, chemical, biological and cognitive processes. Social phenomena are the product of individualsć cognitive processing. They are emergent phenomena, the large-scale effects of locally interacting agents. Interaction is the result of the contingent activity of individuals and a background which is structured on the level of collectivity. In the second part of the paper, research into the cognitive experience of social phenomena is presented. The focus is above all on social neuroscience which observes cognitive processes in functioning brains. Research into sensations, emotions and thoughts of social stimuli is illustrated.
Keywords: Cognitive science; Kognitivna znanost; Sociologija spoznavanja; Sociology of cognition; Social phenomena; Družbeni pojavi; zaznavanje; družbeno zaznavanje